Impact of heavy goods vehicles on safety and traffic management in the Tamale Metropolis - Keketsyor, Mawutor Kofi (2011)
A Thesis submitted to the Department of Civil Engineering, Kwame Nkrumah University of Science and Technology in partial fulfilment of the requirements for the degree of Master of Science, 2008